MiR‐492 regulates metastatic properties of hepatoblastoma via CD44. (25th January 2018) - von Frowein, Julia; Hauck, Stefanie M.; Kappler, Roland; Pagel, Philipp; Fleischmann, Katrin K.; Magg, Thomas; Cairo, Stefano; Roscher, Adelbert; von Schweinitz, Dietrich; Schmid, Irene
Abstract: Background & Aims: MicroRNAs are important genetic regulators of physiological and pathophysiological processes including cancer initiation and progression of hepatoblastoma, the most common liver tumour in childhood. We aimed to identify malignant and metastasis promoting effects of miR‐492, a miRNA, previously reported to be overexpressed in metastatic hepatoblastoma. Furthermore, we intended to evaluate its diagnostic and prognostic potential. Methods: Stable and transient overexpression of miR‐492 in two liver tumour cell lines HepT1 and HUH7 was used to analyse features of metastatic tumour progression such as proliferation, anchorage‐independent growth, migration and invasion. Via a mass spectrometry based proteomic screen, we investigated miRNA‐492‐dependent effects on proteome level and explored the underlying biology. One of the predicted target genes, CD44, was experimentally validated via luciferase assays. Diagnostic and prognostic properties of miR‐492 were studied in hepatoblastoma tumour samples. Results: We show that miR‐492 significantly enhances cell proliferation, anchorage‐independent growth, migration and invasion of hepatoblastoma cells. We also identified and validated CD44, a transmembrane adhesion receptor for hyaluronan, as direct and functional target of miR‐492. This miRNA has a strong direct impact on two CD44 isoforms (standard and v10). High miR‐492 expression correlates with high‐risk or aggressive tumours and further bears potential for predicting reduced event‐free survival. Conclusions: We identified miR‐492 and its target CD44 as regulators of a number of biological features important for malignancy and metastasis. Furthermore, we demonstrated the diagnostic and prognostic potential of miR‐492, a promising novel therapeutic target and biomarker for hepatoblastoma.